HAK DAN KEDUDUKAN ANAK LUAR NIKAH YANG DIAKUI TERHADAP WARISAN TANAH DITINJAU DARI HUKUM PERDATA - Hijawati, Hijawati; Rizayusmanda, Rizayusmanda (Faculty of Law, University of Palembang, 2021)
This writing is done with the aim of knowing how the provisions of children outside of marriage are recognized according to the Civil Code (KUHPerdata) and how the rights and positions of children outside marriage are recognized as inheritance according to the Civil Code. By using the normative juridical research method, it can be concluded that every child born outside of a legal marriage bond is a child outside of marriage. Based on the provisions of the Civil Code, children outside of marriage are deemed not to have any legal relationship with their parents if there is no acknowledgment from the father or mother, thus if the outside child is recognized and followed by the legalization of the child from the parents, then he or she can inherit the inheritance from the parent. admit it, and of course the distribution of inheritance based on law. Based on the Marriage Law, namely Law Number 1 of 1974 (Article 43 paragraph (1)), even illegitimate children who are not recognized automatically have a civil relationship with their mother and their mother's family. The rights and position of out-of-wedlock children in relation to the inheritance of the parents who admit it on the child legitimacy are basically the same as the legal children. The recognized and legalized illegitimate child is truly an heir who has the same rights as a child born in a legal marriage. Judging by civil law, the distribution of inheritance has been determined based on the groups of heirs.